IMPLEMENTATION OF PROJECT-BASED LEARNING IN BASIC EDUCATION MANAGEMENT: ENHANCING CREATIVITY AND SKILLS IN THE 21ST CENTURY - Supriatna, Dasep (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
This study investigates the implementation of Project-Based Learning (PBL) in basic education management to enhance creativity and 21st-century skills[2] among students aged 10 to 14. Grounded in constructivist and sociocultural theories[1], the research employs a mixed-methods approach to evaluate the impact of PBL on creativity, critical thinking, collaboration, and problem-solving. Results indicate significant improvements in cognitive engagement, teamwork dynamics, and innovative problem-solving abilities. Challenges were addressed through targeted scaffolding, highlighting PBL’s adaptability and transformative potential in fostering essential skills for modern educational demands.